Media Consumption of People of Jaffna during Corona Pandemic: A Study Based on Uses and Gratifications Theory - Sivatharshiny, P.; Thulaparani, M.; Raguram, S. ('Jathika Maadhya Sankathana', Academic Journal, Vol.1 Number 2, Ministry of Mass Media, Government of Sri Lanka, 2022)
From the early days till today every human being is engaged in communication in order to fulfill his/her needs. In historical landmarks where he/she tried to expand the communication process, the media has evolved with the development of technology such as print, electronic, new and social media. In this development path, due to the extraordinary situation created by the Corona epidemic that occurred in the last two–three years, people stagnated at one point. Industries and relevant activities that were running were suspended. The people on the mobilization resorted to the stage of stalemate under the compulsion of circumstances. In this context, the media consumption, purposes, uses, the effects of it on the lifestyles and education systems, and the challenges faced by the people of Jaffna have been studied by the researchers with the light of the uses and gratifications theory. Television and social media such as Facebook, WhatsApp, Viber and YouTube have been traced for the first fourteen months of the Corona epidemic for this purpose. Based on that, the consumption of social media has increased in life and education systems among the Jaffna community in the crisis environment identified through the study. Further, it has also been known through research that the rituals related to the life-cycle and educational methodologies move towards the virtual platform during the time of crisis, and moreover, the local people shifted their media consumption from traditional to new media platforms for their entertainment and pleasure, to get world information and news, to relieve their loneliness, to bring out their creative abilities and to continue learning the world activities. At the same time, the study explored the physical and psychological effects, non-liveliness communication between relationships, lack of sufficient technical knowledge and moral discipline to handle social media, lack of sufficient financial means to own media gadgets such as smartphones and computers, addiction to social media, conflicts in personal relationships are observed as negative impacts due to this situation.
Keywords: Corona Pandemic; Jaffna Community; Media Consumption; Uses and Gratifications